2009
DOI: 10.1063/1.3056398
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of a laser prepulse on the proton generation between plastic and metal targets irradiated by an ultraintense laser pulse

Abstract: The effect of a laser prepulse on the generation of proton beams is compared between plastic and metal targets by irradiating a 30fs, 2.4×1018W∕cm2 Ti:sapphire laser pulse. Proton energies generated from both target materials increase as the pulse duration of the laser prepulse decreases. However, it was found that there are distinct differences with respect to target materials. In the case of aluminum targets, as target thickness decreases, proton energy gets higher, which is well described by an isothermal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…For the parameters used in the simulation, the Debye length is estimated to be k De ' 0:25 lm, which is obtained for a laser absorption fraction of 23%. 34,35 Then, the corresponding layer thicknesses are d 1 ¼ 20k De and d 2 ¼ d g ¼ 1:6k De , being similar with the target condition used in the fluid analysis. Layer I is initially positioned at 10 lm away from the left boundary of the simulation box where the laser pulse is launched.…”
Section: Particle-in-cell Simulationmentioning
confidence: 92%
“…For the parameters used in the simulation, the Debye length is estimated to be k De ' 0:25 lm, which is obtained for a laser absorption fraction of 23%. 34,35 Then, the corresponding layer thicknesses are d 1 ¼ 20k De and d 2 ¼ d g ¼ 1:6k De , being similar with the target condition used in the fluid analysis. Layer I is initially positioned at 10 lm away from the left boundary of the simulation box where the laser pulse is launched.…”
Section: Particle-in-cell Simulationmentioning
confidence: 92%
“…Lee et al 15 also observed how the maximum proton energy varies on the laser pre-pulse for target materials and thickness. As shown in Fig.…”
Section: Proton Beams From Plastic Targets: Arie Modelmentioning
confidence: 92%